On ghosts and fairies. Symbolist eroticism, "mágica" and poetics in "Soledades" by Antonio Machado - Gamoneda Lanza, Amelia (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Ghosts and fairies ―those dubious incarnations of eroticism― that populate Soledades, by Antonio Machado, are part of the literary heritage shared by a variety of symbolist poets. This paper looks into this through line from a comparative analysis of French and Spanish poems. Later on, the paper focuses on how these beings, who inhabit or provoke an order of alternation between appearance and disappearance, display different variants of the Barthesian entrebaillement. Such variants can be understood from a perceptive-cognitive perspective, and among them we can also include magic. The fact that Machado has thought his poetics as a kind of "magic" invites us to consider the possible relation between and among his conception of poetic language, the Bergsonian influence, and theoretical symbolist assumptions from the perceptive-cognitive modes suggested by magic and eroticism.
Keywords: Machado; symbolism; ghost; magic; poetics